Baicalin, a Potent Inhibitor of NF-κB Signaling Pathway, Enhances Chemosensitivity of Breast Cancer Cells to Docetaxel and Inhibits Tumor Growth and Metastasis Both In Vitro and In Vivo - Zeng, Anqi; Liang, Xin; Zhu, Shaomi; Liu, Chi; Luo, Xiaohong; Zhang, Qinxiu; Song, Linjiang (Frontiers in Pharmacology, 2020)
Objective: The aim of this study is to investigate the anti-cancer activity and sensibilization of baicalin (BA) against breast cancer (BC) cells. Methods: The anti-proliferation of BA in BC cell lines was evaluated by MTT and colony formation assays. Apoptotic induction of BA was measured by flow cytometry. Wound-healing and transwell assays were exploited to assess migrated and invasive inhibition of BA. Western-blot and immunofluorescence were used to study mechanisms of anti-migration and sensibilization of BA. Anti-tumor and anti-metastasis effects of BA were evaluated in subcutaneous and pulmonary metastasis mouse model of BC cells. Results: BA significantly suppressed proliferation and induced apoptosis of BC cells in a concentration- and time-dependent manner. Additionally, BA induced cell apoptosis via the mitochondria-mediated pathway, as evidenced by cellular induction of reactive oxygen species and upregulated expression of the Bax/Bcl-2 ratio. The NF-κB signaling pathway in BC cells was dramatically inhibited by treatment with BA, thereby suppressing the migration and invasion of BC cells. Notably, BA sensitized BC cells to docetaxel (DXL) by suppressing the NF-κB/survivin signaling pathway. BA also retarded tumor growth and triggered apoptosis of tumor cells in a tumor mouse model of 4T1 cells by inhibiting activation of the NF-κB signaling pathway. Furthermore, pulmonary metastasis of BC cells was distinctly suppressed in a tumor mouse model of 4T1 cells. Conclusion: BA effectively triggered apoptosis, inhibited metastasis, and enhanced chemosensitivity of BC via the NF-κB signaling pathway, implying that BA might serve as a promising agent for the treatment of BC.